Manejo nutricional de traíras em diferentes sistemas de criação - Marasca, Samuel (2022)
There are several species of native fish with productive potential, the trahira (Hoplias malabaricus) being one of them. However, for an intensive production of the species, there is a need for more information about its adaptation in intensive rearing systems and for the acceptance of formulated diets. In this study, the influence of different rearing systems and different feeding training strategies on performance and biochemical parameters, morphometric indices and body composition of trahira juvenile was evaluated. For this, three experiments were carried out. The first (I), lasting 30 days, evaluated different rearing systems (RAS: water recirculation system and BFT: bioflocs) in the cultivation of trahiras juvenile. The second (II), lasting 28 days, in addition to assessing changes in fish reared in RAS and BFT, evaluated two forms of training strategies. The third (III), lasting 70 days, was divided into two phases, the first referring to two forms of training strategies for juveniles, with the objective of training the trahiras to be fed exclusively with 55% crude protein ration and in the second phase, the fish received only feed in order to define the best form of training strategies for the species in question, cultivated in RAS and BFT. The results obtained in experiment I, with trahira juvenile of 0.58±0.12 g, showed that BFT is a viable alternative for the cultivation of trahira in the initial stages of life, presenting productive benefits for the species in this stage of life. Experiments II and III, with trahira juvenile weighing 4.15±0.87 g, showed that both RAS and BFT are viable alternatives for rearing the species. In experiment II, it was also possible to verify that feeding trahiras with feed mixed in gradually increasing proportions in bovine liver brings benefits in relation to feeding only with the liver. In experiment III, it was verified that the correct training strategies, mixing the ration in gradually increasing proportions in the bovine liver for the feeding of trahira juveniles, brings productive and health benefits for these fish.